Histone demethylase JMJD1C promotes the polarization of M1 macrophages to prevent glioma by upregulating miR‐302a - Chuanhong Zhong (Wiley, 2021)
Abstract Glioma is regarded as an aggressive lethal primary brain tumor. Jumonji domain containing 1C (JMJD1C) is a H3K9 demethylase which participates in the progression of various tumors, but its specific function and underlying mechanism in glioma development remain undefined, which is the purpose of our work. We initially assessed JMJD1C expression in glioma tissues and cells using the assays of RT‐qPCR and immunohistochemistry. Meanwhile, the H3K9 level at the microRNA (miR)‐302a promoter region was measured by chromatin immunoprecipitation assay, while luciferase‐based reporter assay was performed for validation of the binding affinity between miR‐302a and methyltransferase‐like 3 (METTL3). The effect of METTL3 on suppressor of cytokine signaling 2 (SOCS2) was subsequently analyzed by MeRIP‐RT‐qPCR. Finally, a xenograft tumor model was established in nude mice, followed by measurement of tumor‐associated macrophages using flow cytometry. JMJD1C was poorly expressed in glioma tissues. Furthermore, JMJD1C increased miR‐302a expression through promoting H3K9me1 demethylation at the miR‐302a promoter region. miR‐302a was identified to target METTL3, which could inhibit SOCS2 expression via m6A modification. JMJD1C promoted M1 macrophage polarization and suppressed the growth of glioma xenografts through the miR‐302a/METTL3/SOCS2 axis both in vivo and in vitro. In conclusion, JMJD1C could enhance M1 macrophage polarization to inhibit the onset of glioma, bringing a new insight into the contribution of JMJD1C to the pathobiology of glioma, with possible implications for targeted therapeutic method.